Предмет: Алгебра,
автор: XyluGUN228
Уравнение решить надо
2x+6(1-x) = -3x+10
3x+4(9+x) = 2x-6
9x+7(-1-3x) = -2x+1
-2x+3(5-7x) = 2x-9
Ответы
Автор ответа:
0
2x+6(1-x) = -3x+10
2x+6-6x=-3x+10
2x-6x+3x=10-6
-x=4
3x+4(9+x) = 2x-6
3x+36+4x=2x-6
3x+4x-2x=-6-36
5x=-42
x= -8
насчет первого не уверена)
2x+6-6x=-3x+10
2x-6x+3x=10-6
-x=4
3x+4(9+x) = 2x-6
3x+36+4x=2x-6
3x+4x-2x=-6-36
5x=-42
x= -8
насчет первого не уверена)
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Английский язык,
автор: aliohinastya
Предмет: Қазақ тiлi,
автор: hdjdjsjkzks
Предмет: Литература,
автор: zhaneldemesheva
Предмет: Математика,
автор: alibzhanova03